Preliminary studies on the lifecycle of Catostylus tagi: differentiation between female and male at morphological level - Lisboa, Raquel (2018)
Poster presented at the 2nd International Congress of CiiEM: “Translational Research and Innovation in Human in health Sciences”. Egas Moniz, Caparica, 11-13 June 2017